PELAYANAN: SEBUAH PRAKTIK SOSIAL AVIATION SECURITY DI PENERBANGAN INTERNASIONAL T3 SOEKARNO-HATTA (STUDI KASUS PEMAHAMAN PENUMPANG TERHADAP PELAYANAN AVSEC) - Nanik Rianandita Sari; Yayu Sri Rahayu; Kartika Fajar Nieamah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Density of activity in the airport is needed security quite tight, considering many users and no users are passing on the airport. To support the security and safety of the flight of an airport there are several requirements that must be fulfilled by airport management. The purpose of this study are: a) To know to understand social practices that occur between Aviation security (Avsec) officers to passengers at T3 Soekarno-Hatta Airport, b) To know the understanding level and passenger satisfaction of service Avsec in T3 Soekarno-Hatta Airport measured from the dimension of service quality tangibles, reliability, responsiveness, assurance, and empathy. The method used in this research is case study. To know the relation of understanding and passenger satisfaction to Avsec service, Double Regression Test has been done, with α = 0.025, result is Tangibles 0.993, Reliability 0.981, Responsiveness 0.027, Assurance 0.117, Empaty 0.0117. From these results, the conclusion of the quality service there is no influence on the Satisfaction Variables. Thus either the passenger understands or does not understand, does not affect the service of Avsec.